2021
DOI: 10.1002/adma.202105882
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrarobust and High‐Performance Rotational Hydrodynamic Triboelectric Nanogenerator Enabled by Automatic Mode Switching and Charge Excitation

Abstract: The triboelectric nanogenerator (TENG) is an emerging technology for ambient mechanical energy harvesting, which provides a possibility to realize wild environment monitoring by self‐powered sensing systems. However, TENGs are limited in some practical applications as a result of their low output performance (low charge density) and mechanical durability (material abrasion). Herein, an ultrarobust and high‐performance rotational TENG enabled by automatic mode switching (contact mode at low speed and noncontact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(64 citation statements)
references
References 40 publications
1
63
0
Order By: Relevance
“…These distributed sensors drive urgent demand and bring huge challenge to distributed and sustainable power supply [5][6][7][8]. Fortunately, triboelectric nanogenerator (TENG), as a new energy converter, provides a promising effective technique for scavenging low frequency mechanical energy, such as vibration energy [9][10][11], wind energy [12][13][14], water flow energy [15,16] and converting into electric energy. Besides, TENG shows great merits in large scale applications for IOTs, BD, and environmental monitoring, such as cost-effectiveness, abundant materials availability, simple structure design, and environmental friendliness [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…These distributed sensors drive urgent demand and bring huge challenge to distributed and sustainable power supply [5][6][7][8]. Fortunately, triboelectric nanogenerator (TENG), as a new energy converter, provides a promising effective technique for scavenging low frequency mechanical energy, such as vibration energy [9][10][11], wind energy [12][13][14], water flow energy [15,16] and converting into electric energy. Besides, TENG shows great merits in large scale applications for IOTs, BD, and environmental monitoring, such as cost-effectiveness, abundant materials availability, simple structure design, and environmental friendliness [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…As demonstrated in our previous works, 16 the wireless data transmission circuit has a regulated two-stage energy management system to efficiently collect and store the generated energy from the nanogenerator. The UTHNG was excited at 6 Hz, and the electric charges were stored in an input capacitor (C in ) of 1 μF (black curve of Figure 7d(ii)).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the previously reported modeswitching works, our device shows good stability and has a lower separation threshold (Figure 2g; Table S2, Supporting Information). [26,27,30,31] After the continuous operation of AB-TENG for 48 h, the optical microscope photographs of PVC surface under automatic switching mode, separation mode, and contact mode are shown in Figure 3f. It is observed that after continuous operation for a long time, the PVC surface is not worn under separation mode, and there are many impurities on the PVC surface under contact mode, and the material is seriously worn.…”
Section: Output Performances Of the Ab-tengmentioning
confidence: 99%
“…[22] It is especially suitable for collecting rotating mechanical energy. In reality, due to the uncertainty of environmental energy, TENG usually works at a higher speed when the collected energy increases (such as irregular airflow, [23][24][25][26][27] water flow, [28][29][30][31] etc. ), and the decline of electrical output performance caused by material wear caused by high speed is an unavoidable problem in practical use.…”
mentioning
confidence: 99%